Global Citizenship: Cultural, Religious and Spiritual - An Exploratory Scoping Review - Millar, CaraJane (Journal of religion and health, 2024)
This paper seeks to provide an exploration of the interplay between global citizenship, culture, religion and spirituality. Arksey and O'Malley's (Int J Soc Res Methodol 8(1):19-32, 2005) scoping literature review framework was utilised to qualify the research question, develop inclusion and exclusion criteria, select relevant studies, chart data and collate information. From the available peer-reviewed literature, a total of 44 articles were initially identified using the selection criteria, 19 of which were subsequently analysed. Eight main themes were identified within the literature; (1) development of global citizenship identity, (2) prosocial values and perspectives, (3) cultural competence and influence, (4) religion and religious teachings, (5) immersion experiences, (6) normative influence, (7) political compass and (8) spirituality. The literature suggests a clear link between global citizenship and spirituality. There were, however, some inconsistencies in the relationship between formalised religion and global citizenship across the studies, with evidence of religion both contributing to and detracting from prosocial values related to global citizenship. Additionally, cultural experiences, including immersion experiences, volunteering and study aboard were all positively linked to prosocial values related to global citizenship. Global citizenship provides individuals with an opportunity to develop intercultural skills, respect, sensitivity, empathy and concern for all of humanity. It is recommended that future global citizenship research should ensure adequate definitions of religion and spirituality, with caution to not generalise the two terms into one concept. Additional research into the relationship between spiritualty and global citizenship could provide a strong basis to increase understanding of the contributing factors to global citizenship identity.